60‐2: Panel Design Technology for a 31‐inch GOA Drived AMOLED Display with BYYB OLED Structure and Slim Border. Issue 1 (29th May 2019) - Xue, Yan; Fang, Chun-Hsiung; Han, Bai-Xiang; Tu, Ai-Guo; Yang, Zhong-Guo; Chaw, Gary; Liao, Cong-Wei; Zhang, Sheng-Dong; Wu, Yuan-Chun; Lu, Po-Yen
Abstract : A much complicated structure, where GOA circuits were placed at the bottom side, was proposed for a 31‐inch AMOLED display. This structure contributed significantly to border reduction and reliability improvement. What's more, amorphous‐indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film‐transistors (TFTs) with top‐gate structure exhibited high performance and the GOA circuits could operate well.